Evaluation of Constipation - Alame, Amer M.; Bahna, Heidi (Clinics in Colon and Rectal Surgery, 2012)
The evaluation of the chronically constipated patient is multifaceted and challenging. Many clinicians define constipation according to the latest Rome III diagnostic criteria for functional gastrointestinal disorders. Female sex, older age, low fiber diet, a sedentary life style, malnutrition, polypharmacy, and a lower socioeconomic status have all been identified as risk factors for functional constipation. In elderly patients, it is important to rule out a colonic malignancy as the cause of constipation. The initial evaluation of the constipated patient includes a detailed history to elicit symptoms distinguishing slow transit constipation from obstructive defecation. Slow transit and obstructive defecation are the two major subtypes of functional constipation. In addition, the clinician should identify any secondary causes of constipation. The office examination of the constipated patient includes an abdominal, perineal, and a rectal exam. Many patients improve with lifestyle modification. When dietary interventions and lifestyle modifications fail, many diagnostic studies are available to further evaluate the constipated patient. Sitzmark transit study, nuclear scintigraphic defecography, electromyography, anorectal manometry, balloon expulsion test, paradoxical puborectalis contraction, cinedefecography, and dynamic magnetic resonance imaging defecography have all been used to diagnose the underlying causes of functional constipation.
Keywords: evaluation of constipation; causes of constipation; radiopaque marker study; anorectal manometry; defecography